1982
DOI: 10.1139/v82-129
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and vibrational study of a 1:1 stoichiometric complex of hydronium tetrafluoroborate and 1,4,7,10,13,16-hexaoxacyclooctadecane (18-crown-6)

Abstract: . Can. J. Chem. 60,853 (1982). The macrocyclic ether 1,4,7,10,13,16-hexaoxaoctadecane (18-crown-6) has the remarkable property of being able to transfer the hydronium (H,O+) ion from an aqueous solution to an organic medium. This property has been used to synthetize a 1:l stoichiometric complex of this ether with hydronium tetrafluoroborate. This complex is very stable (mp 145°C) and dissolves readily, without decomposition, in solvents such as CHCI,. The presence of the H 3 0 + and BF4-ions in the complex has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…The analyses are in agreement with the stoichiometries defined by reactions [I.] and [2] and with that observed in the X-ray determination for the palladium complex.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The analyses are in agreement with the stoichiometries defined by reactions [I.] and [2] and with that observed in the X-ray determination for the palladium complex.…”
Section: Resultssupporting
confidence: 88%
“…This type of complexation was first observed for the cis-syn-cis-dicyclohexano-18-crown-6 with H30+C104-or H30+PF6- (1). In recent years, it has been shown that 18-crown-6 is a good complexing agent for the hydronium ion, and complexes have been obtained with several strong acids (2)(3)(4)(5)(6)(7). In these studies, it was generally assumed that the H30+ ion in the adduct is located at the center of the macrocyclic ether cavity, as this would maximize the electrostatic interactions between the two units.…”
Section: Introductionmentioning
confidence: 76%
“…This rctlects the instability of the complex, particularly towards moisturc. Although the analysis suggests an incomplete complexation between NOIBF, and 18C6, the Raman spectrum of the solid complex, which is discussed below, gives no evidence for the presence of uncomplexed 18C6, whose spectrum is vcry characteristic (4). For the infrared, hexachlorobutadienc.…”
Section: Methodsmentioning
confidence: 93%
“…Both complexes can be hydrolyzcd to the corresponding hydronium conlplex, H30'BF,-. 18C6 (4). with a >95% yield.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation